2017
DOI: 10.1140/epje/i2017-11596-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA sequence in nucleosome breathing

Abstract: Abstract.Roughly 3/4 of human genomes are sequestered by nucleosomes, DNA spools with a protein core, dictating a broad range of biological processes, ranging from gene regulation, recombination, and replication, to chromosome condensation. Nucleosomes are dynamical structures and temporarily expose wrapped DNA through spontaneous unspooling from either end, a process called site exposure or nucleosome breathing. Here we ask how this process is influenced by the mechanical properties of the wrapped DNA, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 65 publications
3
43
0
Order By: Relevance
“…We found significant differences between the dynamics of the 3 nucleosomes, the nucleosome with most TF binding sites showing the largest amplitude of breathing and twisting motions. This is in agreement with previous studies that revealed the more dynamic nature of natural nucleosomes 13,22,28 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found significant differences between the dynamics of the 3 nucleosomes, the nucleosome with most TF binding sites showing the largest amplitude of breathing and twisting motions. This is in agreement with previous studies that revealed the more dynamic nature of natural nucleosomes 13,22,28 .…”
Section: Discussionsupporting
confidence: 94%
“…Despite the lack of full sampling convergence, we observed a good overlap between independent simulations for nucleosome breathing (Fig 3) and we achieved a wider conformational sampling by combining independent simulations of the same species into ensembles. This enabled us to study both breathing and twisting motions in the nucleosomes and to conclude about the sequence dependence of these motions at a level of detail not feasible in coarse grained simulations, which were previously used to study nucleosome dependent dynamics 22,28 . The atomic resolution provides the means to study the determinant modulators of nucleosome dynamics such the motion of histone tails or the role of anchoring histone residues 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the information in these curves provides insight into how this DNA is released from the histone core. The cumulative unwrapping distribution curve (left) reports that mostly wrapped structures are released at the ends (total numbers of basepairs unwrapped less than $40), consistent with breathing modes previously reported (41). For n T values of $40-60, the curve is relatively flat, suggesting that there are few structures in this region.…”
Section: Widom 601supporting
confidence: 85%
“…[18,31]), translational positioning [6] (see Refs. [3,32,33]), sequencedependent nucleosome breathing [34] (see Refs. [35,36]), and force induced unwrapping [23,37] (see Ref.…”
Section: Modelmentioning
confidence: 99%